Transnational practices of Kazakh repatriates: the role of family in the adaptation of ethnic Kazakh students from Mongolia and China - Zharkynbekova, Sholpan; Tazhibayeva, Saule; Shakhputova, Zukhra; Agabekova, Zhazira; Azamatova, Ariya; Kuzar, Zhanna (Frontiers in Sociology, 2024)
Migration processes, which intensified in the late twentieth and early twenty-first centuries, occur within a context of constant challenges and changing realities, necessitating new research in this area. Nearly all migrants, adapting to new forms of everyday existence, might experience socio-psychological stress. This study focuses on the socio-cultural and linguistic adaptation of the young generation of ethnic Kazakhs, as well as their psychological state within the educational environment, grounded in the concept of transnationalism. The authors conducted a survey and interviews with repatriate students from China and Mongolia in their native language, Kazakh. The research methodology, survey methodology and applied tools are comparable in terms of both qualitative and quantitative analysis. The sample population consisted of 230 respondents from five regions, aged between 16 and 25 years old. Furthermore, 30 qualitative, focused interviews were conducted. The discussion questions are related to several important factors, including the impact of the presence of relatives in the country of origin, the establishment of ties with them, and the integration of individuals into the social spheres of their historical homeland during their stay in Kazakhstan, as well as the processes of adaptation and integration into the new society. The results demonstrate the existence of transnational practices among the informants, which permits the categorization of these individuals as transnational migrants, despite the fact that a considerable number of them have completed the migration process. The findings of the research also indicated that repatriate students from Mongolia showed greater ease of adaptation in Kazakhstan, largely due to their more active communication with relatives and stronger inclination toward integration into local society. Conversely, Kazakh ethnic students from China, despite using contemporary communication technologies, encountered more challenges, largely due to emotional difficulties associated with the lack of physical proximity to their families and a prevalent intention to return to their families after graduation.